2017
DOI: 10.1111/jopr.12661
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Intentional Overload on Joint Stability of Internal Implant‐Abutment Connection System with Different Diameter

Abstract: Implants with Ø 5.0 diameter demonstrated significantly low axial displacement and reverse torque loss after the cyclic and static loading of overload condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…Most of the studies related to axial displacement [1][2][3] are on the magnitude of tightening torque and the duration of cyclic loading, and few studies have applied with static loading. Ko et al [4] reported that axial displacement and reverse torque loss occurred at significantly low levels after the cyclic and static loading in the case of wide-type implants of 5.0 mm diameter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the studies related to axial displacement [1][2][3] are on the magnitude of tightening torque and the duration of cyclic loading, and few studies have applied with static loading. Ko et al [4] reported that axial displacement and reverse torque loss occurred at significantly low levels after the cyclic and static loading in the case of wide-type implants of 5.0 mm diameter.…”
Section: Discussionmentioning
confidence: 99%
“…Attempts have been made to understand the factors that could compromise the settling effect of different implant abutment connections [1,2]. Various implant elements including the implant-abutment interface, the types of abutments, the screw characteristics, and the cyclic loading condition have all been shown to influence settling into implants and a loss of preload [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The most important reason to investigate the stress distribution in abutments and microstrain in crestal bone around implants is the possibility to provide sufficient information for implant planning, optimizing the implant installation in areas with different bone characteristics ( 11 ). In spite of this, masticatory overload is one of the primary factors for fractures and dental implant loss ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies carried out with finite element (FE) models have shown that more than 86% of the tightening torque and over 98% of the relaxation torque are balanced by the conical joint of these systems [42]. Generally, most studies dealing with axial displacement do this during cyclic loads [30,43] and few studies have dealt with static loading. Ko et al [44] reported that axial displacement and removal force dramatically decrease as a result of cyclic loading.…”
Section: Discussionmentioning
confidence: 99%